1987
DOI: 10.1021/ef00002a001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the pyrolysis of biomass

Abstract: The technique of molecular-beam, mass spectrometric (MBMS) sampling is applied to the elucidation of the molecular pathways in the fast pyrolysis of wood and its principal isolated constituents. The goal is the optimization of high-value fuel products by thermal and catalytic means. The positive-ion mass spectra shown are obtained from real-time, direct sampling of light gases, reactive intermediates, and condensible vapors simultaneously. The cellulose, lignin, and hemicellulose (e.g., xylan) components of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
714
1
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 802 publications
(759 citation statements)
references
References 4 publications
36
714
1
8
Order By: Relevance
“…The acid catalyst can be both the heterogeneous solid acid and the homogenous organic acid products. It has previously been shown that hydroxyacetaldehyde is formed from pyrolysis of carbohydrates [25]. Trace amounts of anhydrosugars were also observed.…”
Section: Catalyst-to-feed Ratiomentioning
confidence: 92%
“…The acid catalyst can be both the heterogeneous solid acid and the homogenous organic acid products. It has previously been shown that hydroxyacetaldehyde is formed from pyrolysis of carbohydrates [25]. Trace amounts of anhydrosugars were also observed.…”
Section: Catalyst-to-feed Ratiomentioning
confidence: 92%
“…The high amount of ash minerals in the straw will have an effect on its thermal degradation behaviour under pyrolysis conditions. Especially alkali metals are known to catalyse the thermal breakdown of carbohydrates [30,31]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Coniferyl aldehyde, isoeugenol, dihydroconiferyl alcohol, 4-vinylguaiacol and vanillin are more important products (in the case of G-lignin pyrolysis). Only direct mass spectrometric analysis of the pyrolyzates from wood and lignin samples, without cooling, indicate significant contributions of coniferyl alcohol (MW: 180) and sinapyl alcohol (MW: 210) [7]. These apparently contradictory observations can be explained by the propensity of coniferyl alcohol and sinapyl alcohol to undergo secondary pyrolysis reactions, particularly polymerization reactions [82][83][84][85].…”
Section: Re-polymerization and Side-chain Conversionmentioning
confidence: 99%